Analisis Faktor Kunci Perpanjangan Kontrak Tenant Di Manado Town Square - moningka, Ritskia frista (JURNAL RISET BISNIS DAN MANAJEMEN, 2019)
This study aims to analyse key factors are considered by the tenants in extending the lease contract at the Mall Manado Town Square. Using factor analysis: confirmatory factor analysis (CFA) and with a total sample of 157 tenants in the Manado Town Square Mall, submitted 23 variables related to the extension of tenant rental contracts. The results of the study found that there were 22 valid factors, there were 5 of the most dominant factors affecting the extension of tenant rental contracts, namely: duration and rules of contract extension; availability of elevator and escalator facilities; sanitary facilities and cleanliness; availability of communication network facilities; and the existence of security. Through this research, 6 key factors were considered by the tenants in extending the leasing contract at the Shopping Center, namely: mall performance; convenient facilities; attractive mall; public image; atmosphere and layout; and security of the parking lot. So that these factors are taken into consideration for mall management and further researchKeywords: Confirmatory Factor Analysis; Tenant Mall Contract